Variasi Dimensi Ellipse Silencer terhadap Torsi, Bmep, Kebisingan Mesin Bensin - Bima Samudra Nurrohman; Yuniarto Agus Winoko (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
An exhaust pipe is a tubular device used to channel combustion gases from a vehicle’s engine into the environment. In addition to this primary function, the exhaust also serves to reduce the noise level produced by engine combustion. The component of the exhaust system that significantly affects torque, brake mean effective pressure (BMEP), and noise level is the silencer. This study aims to compare the torque, BMEP, and noise levels produced by variations in the length and construction dimensions of elliptical filter designs in the silencer. The silencers used in this research have lengths of 280 mm, 300 mm, and 260 mm, with short ellipse filter diameters of 25 mm and long ellipse filter diameters of 30 mm, 40 mm, and 50 mm. The research employs an experimental quantitative method, and the data were analyzed using one-way Analysis of Variance (ANOVA). The experiment was conducted in a Mechanical Engineering workshop using a Yamaha R15 V3 155cc injection motorcycle (2021), a Super Dyno 50L dyno test, and a sound level meter, from February to April 2024. The engine speeds tested were 1500, 2500, 3500, 4500, 5500, and 6500 rpm. The results show that the variation of ellipse dimensions 25 mm × 50 mm × 260 mm produced a maximum torque of 12.77 N·m at 4500 rpm, a maximum BMEP of 1021 kPa at 4500 rpm, and a noise level of 80.3 dB. The variation 25 mm × 40 mm × 300 mm produced a maximum torque of 12.88 N·m, a BMEP of 1042 kPa, and a noise level of 75.60 dB, while the variation 25 mm × 30 mm × 280 mm produced a maximum torque of 12.67 N·m, a BMEP of 1013 kPa, and a noise level of 75.63 dB.